Factors Associated with Occupational Injury among Hydropower Dam Construction Workers, South East Ethiopia, 2018. (27th April 2020) - Hussen, Jemal; Dagne, Henok; Yenealem, Dawit Getachew
Abstract : Background . Occupational injuries pose a major public health and socioeconomic developmental problems. Globally, 160 million people encounter occupational injuries; the International Labour Organization estimates that the cost is 4% of the global gross domestic product (GDP) or 1.25 trillion United States Dollar (USD). The second-largest number of occupational injuries was reported from the construction industries. There are limited studies about the prevalence and factors associated with occupational injuries among dam construction workers in Ethiopia. Hence, this study was undertaken to determine the prevalence and associated factors of occupational injury among Genale Dawa hydropower dam construction workers. Method . Institutional-based cross-sectional study was conducted in Genale Dawa 3D hydropower dam construction project from April 1 to 22, 2018. Four hundred and five workers were included in the study. An Oromiffa version pretested, semistructured questionnaire was used to collect data. Data were entered into Epi-info version 7, and analysis was done using SPSS version 20 software. Bivariable and multivariate binary logistic regression was used to see the association between predictors and the dependent variable. The 95% CI and adjusted odds ratio with a P value of 0.05 was used to fit the final model. Results . The prevalence of occupational injuries in the earlier 12 months before the study was 57.8% with (95% CI (52.8, 62.7)). Age, educational status, alcohol consumption, job stress, work shift, and working hours per week were factors significantly associated with occupational injury. Conclusion and recommendation . Occupational injuries were common among dam construction workers. Conducting regular monitoring of substance abuse, avoiding overtime work, rotation of the work shift, and considering age and the educational status during employee recruitment can be effective to decrease the prevalence of occupational injuries.